Correlation of Hydronephrosis Index to Society of Fetal Urology Hydronephrosis Scale. (24th February 2009) - Venkatesan, Krishnan; Green, Joel; Shapiro, Steven R.; Steinhardt, George F.
Abstract : Purpose . We seek to correlate conventional hydronephrosis (HN) grade and hydronephrosis index (HI). Methods . We examined 1207 hydronephrotic kidneys by ultrasound. HN was classified by Society of Fetal Urology guidelines. HN was then gauged using HI, a reproducible, standardized, and dimensionless measurement of renal area. We then calculated average HI for each HN grade. Results . Comparing HI to standard SFU HN grade, average HI is 89.3 for grade I; average HI is 83.9 for grade II; average HI is 73.0 for grade III; average HI is 54.6 for SFU grade IV. Conclusions . HI correlates well with SFU HN grade. The HI serves as a quantitative measure of HN. HI can be used to track HN over time. Versus conventional grading, HI may be more sensitive in defining severe (grades III and IV) HN, and in indicating resolving, stable, or worsening HN, thus providing more information for clinical decision-making and HN management.